A revision of Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). V. Algidum, morosum and tectum groups, a new species of the fusculum group, and faunistic records - SHAVRIN, ALEXEY V. (Zootaxa, 2022)
containing European A. algidum (Erichson, 1840) comb.n. (from Deliphrum), the morosum group containing A. morosum sp. n. (Nepal), and the tectum group containing transpalaearctic A. tectum (Paykull, 1789) comb.n. (from Deliphrum Erichson, 1839), Siberian A. frigidum (J. Sahlberg, 1880) comb.n. (from Deliphrum), and seven new species from the eastern Palaearctic Region: A. cornatipenis sp. n. (China: Sichuan, Shalui Shan), A. himalayense sp. n. and A. vitreum sp. n. (Nepal), A. multipunctatum sp. n. (China: Sichuan, Chuangdongzi Mt.), A. smetanai sp. n. (China: Xizang, Quinlai Shan), A. tichomirovae sp. n. (Tajikistan: Gissar Mts.) and A. umbrinum sp. n. (China: Yunnan, Yulong Mts.). The species groups are defined, briefly discussed, and a key to the species of the tectum group is given. Anthobium infractum sp. n., a new species of the fusculum group from India (West Bengal), is described. The genus-group names Deliphrum and Arpediopsis Ganglbauer, 1895 (previously subgenus of Deliphrum) are treated as junior synonyms of Anthobium. All these taxa are re-described, illustrated, and their geographical distribution is mapped. Additionally, faunistic records for seven species of the consanguineum, fusculum, nigrum, and reflexum groups are given. Anthobium frigidum is recorded from Tyumen Area, Khanti-Mansi and Taimyr autonomous regions, Evenkia, Tuva and Buryatia, and A. tectum from Nenets, Khanty-Mansy, Yamalo-Nenets and Jewish autonomous regions, Tver, Sverdlovsk, Chelyabinsk, Tyumen, Novosibirsk, Chita and Amur area, Altai, Evenkia, Tuva, and Khabarovsk Territory for the first time.